The Relationship of College Student and Veteran Identities to Mental Health Symptoms and Alcohol Use Among Veteran and Nonveteran Students. (2nd January 2020) - Lostutter, Ty W.; Neighbors, Clayton R.; Simpson, Tracy; Larimer, Mary E.
Abstract: Although the 9/11 GI Bill gives veterans access to educational benefits, many return from deployment with physical and psychological challenges that may impede academic success. The current study assessed veteran and nonveteran students reports of alcohol misuse and psychiatric symptoms. The study sought to examine how identifying as a veteran and/or a college student might influence the relationship between veteran status and alcohol and psychiatric symptoms. Participants were 184 veteran and 201 nonveteran students, who completed measures of alcohol use and problems, posttraumatic stress disorder (PTSD), generalized anxiety, depression symptoms, and identification with college student and veteran identities. Veterans were less likely to identify with typical college students compared to nonveterans. There were no significant differences in alcohol use, consequences, or PTSD symptoms between veteran and nonveteran students. However, veteran status was associated with lower scores on measures of depression and anxiety. Interestingly, identification with typical students was associated with lower scores on all measures of mental health symptoms. Moderation analyses suggests that higher identification with typical college student identity was associated with fewer PTSD symptoms particularly among veterans. Identification with typical students may be associated with fewer mental health symptoms among college students, particularly veterans returning to college.